People management in times of global health crisis: case study in the city of São Paulo – SP - Santos, Renata dos; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2021)
The pandemic caused by the new coronavirus (COVID – 19) stroked the year 2020 around the globe with countless challenges and uneasiness’s to organizations and general population. This essay objective is pursuing basement in literature to comprehend how to keep workers motivation during a healthy crisis using qualitative approach and comparative method to analyze data under an exploratory aspect through case study at a mental health unit in São Paulo city. The results founded, identified that the organization showed difficulties in managing the team and administrate practical matters, as the way to proceed to keep the team motivated through this pandemic critical period. In this context, some solutions supported by literature where thought out for this organization under study, as follows; implementation of a home office system, person-oriented administration, assertive and continuous communication and worker training and qualification.
Keywords: Motivational factors; management; pandemic; home office